Morphology-controlled CoNi/C hybrids with bifunctions of efficient anti-corrosion and microwave absorption. (10th March 2022) - Ge, Jianwen; Cui, Yu; Qian, Jiaxin; Liu, Li; Meng, Fandi; Wang, Fuhui
Highlights: The electromagnetic response of morphology-dependant porous/hollow hybrids was investigated. Rod-shaped composites are endowed with excellent absorption properties. Samples CoNi/C-r-700 and CoNi/C-d-700 present relatively high E corr and low I corr . Abstract: Till now, fewer literatures have investigated the corrosion resistance of microwave absorbers, especially mental@C/carbon matrix derived from MOF composites, although it is known that carbon shells possess a protective effect. Herein, three kinds of morphology-controlled CoNi/C-N doped architectures were successfully fabricated via a sequence of processing, namely coprecipitation for ZIF-67, subsequent Ni 2+ exchange and ultimate carbonization. Apart from composition characterization, the effects of microstructure tailoring and temperature controlling on electromagnetic response as well as attenuation performance were revealed, where dodecahedron-shaped composites possessed the highest permittivity. By contrast, rod-shaped composites (CoNi/C-r-550 and CoNi/C-r-700) were endowed with superior comprehensive absorption properties, e.g., RLmin : -49.8 dB and -64.0 dB; EAB: 5.7 GHz and 4.8 GHz, respectively. Besides, samples CoNi/C-d-700 and CoNi/C-r-700 present higher corrosion potential ( E corr ) and lower corrosion current ( I corr ). Hence, these corrosion-resistant microwave absorbers with outstanding absorption stability, wetting effect as well as environmental adaptability, can be used as a candidate/raw material for intelligent devices. Graphical abstract: Image, graphical abstract